THE ROLE OF SMART MANUFACTURING IN PROMOTING GREEN MARKETING: AN EXPLORATORY RESEARCH IN THE UNION COMPANY FOR FOOD INDUSTRIES LTD. IN BABYLON - Lecturer Dr. Emad Wahhab Abdel-Amir Al-Husseini; Assistant Lecturer Rana Zaher Salman Al-Janabi (Galaxy International Interdisciplinary Research Journal, 2023)
The research aims to identify the role of smart manufacturing in promoting green marketing at the Union Company for Food Industries in Babil Governorate, and in order to achieve this, the dimensions of smart manufacturing were adopted (operational cognitive intelligence, operational technological intelligence, smart manufacturing environment, operational environmental intelligence), The dimensions of green marketing were also adopted (abolishing or reducing the concept of waste, redesigning the product, clarifying the relationship between price and cost, making the environmental orientation profitable), and Al-Ittihad Company for Food Industries Limited was chosen as one of the largest and most advanced food industry companies in Iraq and one that follows production methods Al-Haditha is an exploratory and analytical field for research by distributing a questionnaire that included (90) respondents from the administration managers and heads of departments and divisions and their units for the research sample factories. The research concluded with a number of recommendations, the most prominent of which was the need to employ the dimensions of the independent variable, smart manufacturing, in enhancing the positive impact relationship between it and the dimensions of the dependent variable, green marketing, within the industrial sector, and in line with continuing to create products of strategic value for industrial enterprises and achieve Environmental sustainability by keeping abreast of developments and seizing opportunities to ensure continuity, growth and survival in the labor market.